Convenient MCRs Synthesis of Trifluoromethylated Pyrano[4,3-b]pyrans and Their Further Transformation - Wang, Wei; Li, Jia; Zhang, Li; Song, Liping; Zhang, Min; Cao, Weiguo; Deng, Hongmei; Shao, Min (Synthesis, 2012)
Ethyl 2-hydroxy-7-methyl-5-oxo-4-aryl-2-(trifluoromethyl)-3,4-dihydro-2H,5H-pyrano[4,3-b]pyran-3-carboxylate derivatives were synthesized via a one-pot three-component reaction (MCR) promoted by ammonium acetate. The effect of ammonium acetate and the solvent on the reaction efficiency was investigated. Furthermore, treatment of the resultant products with thionyl chloride/pyridine in chloroform gave the corresponding dehydrated products ethyl 4-aryl-7-methyl-5-oxo-2-(trifluoromethyl)-4H,5H-pyrano[4,3-b]pyran-3-carboxylates and the unexpected defluorinated products ethyl 3-aryl-6-methyl-4-oxo-4H-furo[3,2-c]pyran-2-carboxylates. The novel products are highly important for the synthesis of related fluorinated fused heterocyclic compounds.
Keywords: MCR; fluorinated heterocycle; ethyl trifluoroacetoacetate; dehydration